2009
DOI: 10.1007/s10048-009-0211-3
|View full text |Cite
|
Sign up to set email alerts
|

Compound Charcot-Marie-Tooth disease may determine unusual and milder phenotypes

Abstract: Compound forms of Charcot-Marie-Tooth (CMT) disease have been recently associated with unusually severe neuropathies, an observation that prompted the proposition that the additive effects of two mutations should be searched in patients whose clinical severity falls outside the common CMT phenotypes. In this report, we present a father and a daughter with a very mild and unusual disease that segregates with two mutations in PMP22 gene, the 17p11.2-p12 duplication and a Ser72Leu point mutation. We propose that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
6
0
2
Order By: Relevance
“…Sometimes, the combination of two different entities results in a more severe phenotype [9,[13][14][15][16][17]. In other occasions, in contrast, multiple mutations may be associated with milder phenotypes [8,18]. The case here reported represents a different scenario in which an unexpected finding has concluded with the diagnosis of two different entities, although the clinical manifestations correspond only to one of the conditions (SMA).…”
Section: Discussionmentioning
confidence: 76%
“…Sometimes, the combination of two different entities results in a more severe phenotype [9,[13][14][15][16][17]. In other occasions, in contrast, multiple mutations may be associated with milder phenotypes [8,18]. The case here reported represents a different scenario in which an unexpected finding has concluded with the diagnosis of two different entities, although the clinical manifestations correspond only to one of the conditions (SMA).…”
Section: Discussionmentioning
confidence: 76%
“…Recent studies suggested that atypical or severe phenotypes of CMT may result from combined effects of multiple mutated genes expressing in the peripheral nerves or in the neuromuscular system [14]. Combinations of CMT1A and the other inherited muscle disorders (Duchenne/Becker muscular dystrophy, facioscapulohumeral muscular dystrophy) with severe phenotype were previously reported in the literature [15][16][17].…”
Section: Discussionmentioning
confidence: 97%
“…They pointed out that the presence of two mutations in the PMP22 gene resulted in attenuation of the individual effects of each mutation. Therefore multiple mutations may be associated not only with more severe forms of disease, but also with milder and/or atypical phenotypes [14].…”
Section: Discussionmentioning
confidence: 99%
“…12 Indeed, compound heterozygosity in CMT can give genesis to atypical phenotypes and should be considered in cases with the standard clinical course. 13 At the same time, MRI findings inevitably raise the question of whether and to what extent mild ventricular dilation and the sacral cyst have contributed to the severity of symptoms. The fact that these conditions have remained unchanged despite the evolution of the patient's symptoms renders this possibility rather unlikely.…”
Section: Discussionmentioning
confidence: 99%